Perancangan Aplikasi Absensi Karyawan Berbasis Mobile Menggunakan GPS (Studi Kasus PT. Trans Retail Indonesia) - Puput Apriadi; Entis Sutrisna (Indonesian Journal Publisher, 2023)
Technology is a device that is used by someone to process data, obtain information, and so on. Technological developments encourage the centralization of computing systems and long-distance communication systems to make it easier for humans to solve various communication problems related to distance. PT Trans Retail Indonesia is a world-class retail company with the trademark Transmart Indonesia. As a large company, this PT utilizes a digital-based attendance record application to record the attendance of its employees. To further enhance the function of the previous application, the author makes the absence application online by providing more effective features. The research method used is the Rapid Application Development (RAD) method and a questionnaire. The results of this study are a prototype of a mobile-based employee attendance application using GPS which has a more effective quality than the previously used online attendance application.